The Contribution of Islamic Bank in Poverty Alleviation - Nugroho, Lucky; Mastur, Akhmad Amien; Harnovinsah, Harnovinsah; Aryanti, Widya (Al-Ahkam, 2020)
The existence of Islamic banks as one part of Islamic financial institutions should contribute to improving the economy, one of which is to reduce poverty. Therefore, the purpose of this study is to investigate the effect of financing variables, asset variables, and Islamic bank office variables on poverty levels. The sample used to be Islamic Commercial Banks (BUS) in the 2013-2017 period, with a total of 110 samples. The methodology used is quantitative with multiple regression statistical analysis and statistical data processing using SPSS software version 20. The results of the study note that financing has a negative and significant effect, namely, the higher the financing of Islamic banks, it will reduce poverty. However, the total assets and the number of networks that have a positive and significant effect, namely the increase in total assets and branch networks, it will affect the increasing amount of poverty. That is because the assets of Islamic banks are supported by the majority savings and the not optimal yet of distribution of financing from Islamic banks to the community. Also, the existence of the Islamic branch office tends to be found in provincial capitals and big cities, so that the communities in rural and remote areas are still not reached by Islamic banks.